Severe hemodynamic instability during elective surgery for a patient with a giant pheochromocytoma: A case report - Hu, J.Y. (Int J Surg Case Rep, 2019)
INTRODUCTION: We present a patient with a huge pheochromocytoma who ran a stormy intraoperative course. PRESENTATION OF CASE: A 57-year-old woman underwent elective open surgery for a giant pheochromocytoma (16 × 15 × 10 cm) after adequate preoperative medical preparation. The patient developed severe hypertension on tumor mobilization followed bylife-threatening hypotensionwhen the tumor was removed. The hemodynamic instability was successfully managed. Histology showed a pheochromocytomawith tumor-free resection margins. The patient fully recoveredandthe hypertension completely resolved after the operation. DISCUSSION: This is a rare and educational case report on a patient with a huge pheochromocytoma who was successfully managed by a multidisciplinary team of specialists. CONCLUSION: Pheochromocytoma should be resected if technically possible. A multidisciplinary team approach is required for proper management.